Unsaturated soil mechanics in engineering practice - Fredlund, D. G. (Delwyn G.), 1940-; Fredlund, Murray D.,1968-; Rahardjo, H. (Harianto) (Hoboken, N.J. John Wiley & Sons, 2012)
"Thoroughly covers the state of the art of unsaturated soil behavior and better reflects the manner in which practical unsaturated soil engineering problems are solved. The fundamental physics of unsaturated soil behavior presented in the earlier book has largely been retained in the proposed book while greater emphasis has been placed on the importance of the "soil-water characteristic curve" in solving practical engineering problems"--
Includes bibliographical references and index
Keywords: Soil mechanics -- Mathematical models; Soil mechanics; Soil moisture; Soils -- Testing